Void of Power - Mancini, Francesco; Glusac, Tanja (2018)
The history of built environment reflects the rise and fall of political systems, their conflicts, the social contradictions and ultimately, the state of being of a particular civic society over time. Former symbols of power, such as ancient monuments, palaces and churches still express today their symbolic, economic, cultural and political value which constituted in different ages the motivation for their being. Today these are replaced by new symbols of contemporary economic forces which through skyscrapers express global tendency and power movements. While physical edifices are easily recognizable as being expressive embodiment of power and political systems of their time, less visible, yet equally potent, are the shifts and voids in power relations. To fully comprehend the role of architecture in expressing and supporting power structures, it is important to question the concept of architecture as a mere act of presence (the construction) and consider instead the void and its complementary aspects: the absence, the erasure and the ideological need for demolition, as expressions of power. This paper therefore considers power within the parameters of void, which extend beyond the notion of “tabula rasa” that has characterized many urban transformations over the years. By considering the emblematic case of Via dell’ Impero (void), analyzing various ‘iconic’ works of architecture for their role in expressing power of institutions and individuals and adding to the recognisability of place (construction), and identifying dispersion as an underhanded way of exercising power, this paper proposes a more complex reading of urban transformations (dispersion of people via gentrification). It offers moments of reflection and a shift in research focus in terms of how the void is used today to express and support present power relations. Key Words: Fascism, Power, Rome, Urban Transformations, Void.